1995
DOI: 10.1159/000147685
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Retromandibular Vein in Relation to the Facial Nerve in the Parotid Gland

Abstract: In order to help avoid complications of parotid surgery, we investigated the relationship between the facial nerve and the retromandibular vein. Fifty dissections were performed on 30 cadavers. In 45 (90%) of the cases the retromandibular vein was located on the medial side of the upper and lower trunks of the facial nerve, and in 5 (10%), the course of the retromandibular vein was lateral to the lower trunks and medial to the upper trunks. These variations were divided into subgroups. The most commonly encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…In this study, the cervicofacial division of the facial nerve arose in relation to the lateral aspect of this vein in 83% of specimens and in relation to the medial aspect in 17%. However, Kopuz et al (1995) and Dingman et al (1962) reported that the cervicofacial division passed across its lateral aspect in over 90% of cases. Lee (1987), studying Korean materials, and Savary et al (1997) reported that the cervicofacial division passed the superficial side of the retromandibular vein in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the cervicofacial division of the facial nerve arose in relation to the lateral aspect of this vein in 83% of specimens and in relation to the medial aspect in 17%. However, Kopuz et al (1995) and Dingman et al (1962) reported that the cervicofacial division passed across its lateral aspect in over 90% of cases. Lee (1987), studying Korean materials, and Savary et al (1997) reported that the cervicofacial division passed the superficial side of the retromandibular vein in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al found that the accuracy of the RMV landmark was higher in patients with tumors <2 cm . Seldom the RMV can run superficially to the FN and lead to misinterpretation of the US findings . Therefore, the relationship of tumors to other anatomical landmarks has also been considered in this study.…”
Section: Discussionmentioning
confidence: 95%
“…In the study of Kopuz et al, [12] it was concluded that the RV lied medial to the FN temporofacial and cervicofacial divisions in 90% (45/50), and in 10% (5/50) the RV course was medial to the temporofacial and lateral to the cervicofacial divisions, whereas in a single case the RV was detected lateral to the nerve, at its bifurcation level. The authors also noticed that in 74% of the cases, the vein crossed the nerve at a level between the bifurcation and ramification points [12]. After examining 85 facial halves in cadavers, Kim et al [11] observed lateral position of the FN cervicofacial division in relation to the vein in 83%.…”
Section: Discussionmentioning
confidence: 95%